Rechargeable Batteries: Materials, Technologies and New Trends - Zhang, Zhengcheng (Springer, 2016)
This book updates the latest advancements in new chemistries, novel materials and system integration of rechargeable batteries, including lithium-ion batteries and batteries beyond lithium-ion and addresses where the research is advancing in the near future in a brief and concise manner. The book is intended for a wide range of readers from undergraduates, postgraduates to senior scientists and engineers. In order to update the latest status of rechargeable batteries and predict near research trend, we plan to invite the world leading researchers who are presently working in the field to write each chapter of the book. The book covers not only lithium-ion batteries but also other batteries beyond lithium-ion, such as lithium-air, lithium-sulfur, sodium-ion, sodium-sulfur, magnesium-ion and liquid flow batteries.